SCREW WITHDRAWAL RESISTANCE OF WOOD-BASED COMPOSITE PANELS (PART I) - Jakimovska Popovska, Violeta; Iliev, Borche; Mihajlova, Julija (Innovation in Woodworking Industry and Engineering design, 2017)
This research includes the screw withdrawal resistance of wood-based composite panels for use in the construction. Three experimental wood-based composite panels were prepared by combining particleboards and peeled beech, black pine and poplar veneers with thickness of 3.2 mm. The core layer of the wood-based composite panels was made of single-layer particleboard with the thickness of 16 mm, which was overlaid on both sides with the veneers. Water-soluble phenol-formaldehyde resin was used for particle bonding and veneering. The screw withdrawal tests were performed according to the principles of the standard MKS D.C8.112/82. The screw withdrawal resistance was tested in two directions: perpendicular to the plane of the panel, and in plain of the panel. The results from the research showed that the different veneer species used for particleboard overlay significantly affected the screw withdrawal resistance perpendicular to the plain of the wood-based composite panels. According to the obtained the screw withdrawal resistance values, wood-based composite panels tested in this study could be recommended for utilizing in the construction of wooden structures.